2015
DOI: 10.3329/dujbs.v24i2.46327
|View full text |Cite
|
Sign up to set email alerts
|

Potential fungicides and plant extracts against Fusarial wilt of brinjal

Abstract: Antifungal potentials of nine fungicides and eight plant parts extracts were tested in opposition to Fusarium oxysporum Schlecht. and F. solani (Mart.) Sacc. – the two pathogens, isolated from wilted roots of brinjal plants. Efficiency gradients observed in the present study expressed that Bavistin and Tall were the best inhibiting agent against the in vitro growth of the test pathogenic fungi. Among aqueous extracts of eight plant parts significant inhibition of the growth of the pathogens was observed with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Greengel and Dithane showed 68.28 and 48.57% growth inhibition of Fusarium solani, respectively at 500 ppm ( Table 2). Bashar et al (14) reported the effects of Bavistin, Dithane and Tall on the radial growth of Fusarium oxysporum and F. solani at 400 ppm only. Chakraborty et al (11) reported that, at 0.5% dose, bavistin happened to be the most efficient one contributing the highest inhibition (83.7%) of growth of the F. solani causing wilt of brinjal under in vitro condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greengel and Dithane showed 68.28 and 48.57% growth inhibition of Fusarium solani, respectively at 500 ppm ( Table 2). Bashar et al (14) reported the effects of Bavistin, Dithane and Tall on the radial growth of Fusarium oxysporum and F. solani at 400 ppm only. Chakraborty et al (11) reported that, at 0.5% dose, bavistin happened to be the most efficient one contributing the highest inhibition (83.7%) of growth of the F. solani causing wilt of brinjal under in vitro condition.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, some workers on the fungi toxicity of extracts of various parts of higher plants have indicated the possibility of their exploitation as natural fungi toxicants for controlling plant diseases (12)(13)(14)(15) . Plant metabolites and plant based pesticides appear to be one of the better alternatives as they are known to have minimal environmental impact and danger to consumers in contrast to the synthetic pesticides (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Various workers in different countries evaluated the efficacy of various fungicides against Colletotrichum spp. and S. rolfsii under laboratory and field conditions (2)(3)(4)(5)(6)(7)(8)(9) . Very few works have been done for the control of anthracnose and soft rot diseases of jute by fungicides and plant extracts.…”
mentioning
confidence: 99%